Beyond Dyads: Regional Democratic Strength's Influence on Dyadic Conflict. Issue 2 (14th March 2016) - McCallister, Gerald L.
ABSTRACT: Over the history of modern international relations research, we have moved from systemic and regional studies to empirical explorations of dyadic interactions. However, our statistical models have put the details of dyadic interactions under a microscope at the expense of ignoring the relevant regional context that these dyads interact in. This development has been in part due to computational limitations, but do we really believe that decision makers interact with one another while ignoring the regional power balance and the wishes of regional powers? In this article, I take a look at the well-researched relationship between democracy and peace by using a multilevel approach to dyadic interactions and the regions they are embedded in. The findings suggest that when the regional power balance favors democracies, it influences conflict between dyads, especially mixed dyads, by increasing the costs of aggression by autocracies and establishing regional norms of cooperation and compromise.